Smooth muscle-specific expression of hydroxyindole O-methyltransferase reduces arterial injury-induced intimal hyperplasia - Wei-Cheng Jiang; Chung-Huang Chen; Hua-Hui Ho; Pei-Yu Gung; Jing-Yiing Wu; Cheng-Chin Kuo; Kenneth K. Wu; Shaw-Fang Yet (Journal of Biomedical Science)
Abstract Background The pineal gland produces melatonin to control circadian rhythm via the final enzyme in the serotonin pathway, hydroxyindole O-methyltransferase (HIOMT). Interestingly, HIOMT is expressed by certain non-pineal cells. The main catalytically active of the three human HIOMT (hHIOMT) isoforms in pineal cells is hHIOMT345 (345 amino acids), while hHIOMT298 (298 amino acids) is the most active isoform in fibroblasts, where it converts 5-hydroxytryptophan to 5-methoxytryptophan (5-MTP). We previously demonstrated that exogenous 5-MTP protects the arteries. Nevertheless, whether vascular smooth muscle cells (VSMCs) per se synthesize 5-MTP is unknown. Methods We transfected primary wild-type VSMCs with different hHIOMT isoforms and treated them with inflammatory cytokines to examine hHIOMT’s effects on p38 MAPK activation. Global and VSMC-specific hHIOMT transgenic mice were generated and subjected to an arterial injury model. Histological analysis was performed to evaluate intimal hyperplasia and expression of select tryptophan metabolites and their synthetic enzymes. We treated wild-type and transgenic VSMCs with interleukin-1 beta (IL-1β), with or without 5-MTP, to examine the levels of serotonin and aromatic L-amino acid decarboxylase (AADC). Serotonin’s effects on VSMC functions were evaluated, and inhibitors of p38 MAPK and ERK1/2 were used to determine the signaling pathways. The effects of AADC on VSMCs were assessed by AADC knockdown or overexpression. Results Overexpression of the human full-length isoform of 373 amino acids (hHIOMT373) in VSMCs attenuated proinflammatory cytokine-induced p38 MAPK activation, similar to 5-MTP treatment. Global and VSMC-specific hHIOMT373 transgenic mice exhibited attenuated intimal hyperplasia following arterial injury. Intriguingly, the tryptophan metabolite serotonin and its synthetic enzyme AADC were reduced in transgenic arteries. In VSMCs, IL-1β increased AADC and serotonin levels that were mitigated by 5-MTP treatment or HIOMT overexpression via suppressing the p38 MAPK pathway. Interestingly, serotonin promoted VSMC proliferation and decreased VSMC marker levels through ERK1/2 activation. While AADC overexpression decreased VSMC contractile markers, AADC knockdown suppressed IL-1β-induced VSMC proliferation. Conclusions Our results unveiled a unique function of HIOMT in vascular disease. In VSMCs, hHIOMT373 reprogrammed tryptophan metabolism to increase 5-MTP and decrease serotonin levels, thereby protecting against injury-induced intimal hyperplasia. Mechanistically, HIOMT-5-MTP suppressed AADC-serotonin induction through inhibiting p38 MAPK activation.